EFEKTIVITAS UNIT KEGIATAN MAHASISWA RIJAL RISET DALAM PENINGKATAN KARYA TULIS ILMIAH (Studi Analisis Mahasiswa Prodi Hadits STDIIS Jember) - Sanusin Muhammad; Sucipto (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2019)
Extracurricular activities are student activities that include reasoning and science, interests and hobbies, efforts to improve student welfare and social service for the community. In this regard, STDI Imam Syafi'i Jember participated in developing the interests and talents and potential of students to be able to compete in the era of globalization. One of the student activity units formed was the Research Rijal Student Activity Unit. Research on this UKM is needed. The reason is because the making of scientific papers that are the product of this unit is a hard thing for students in general.This study aims to explain the cause of students lack of interest in making scientific papers, factors driving students to join Research Rijal UKM, and the contribution of these UKM in improving scientific writing. This research uses a qualitative approach with the type of case study. Data is described descriptively. The analysis used is inductive analysis. Based on its scope, this study takes one site. Data was collected from several documents, observations, and interviews with 17 informants. The main informants in this study were 13 students of the Hadith Sciences Study Program. Then supplemented with additional informants from 3 Ahwal Syakhsiyah Study Program students and P3M supervisors.This research produces several conclusions. First, that the cause of students' lack of interest in making scientific papers is because: (a) students are less interested in writing, (b) lack of ideas and ideas, and (c) the rules for writing scientific papers that are relatively complicated. Second, the factors driving the students of the Hadith Science Study Program to join Research Rijal UKM include: (a) they want to learn the methodology of writing scientific papers, (b) foster interest in reading, (c) practice critical habits of scientific papers, and (d ) develop general writing skills. Third, the contribution of UKM Rijal Research includes (a) giving special lectures to UKM members on how to make good scientific journals and (b) providing further guidance in the completion of scientific papers.